Agreement Between the KTK3+ Test and the Athletic Skills Track for Classifying the Fundamental Movement Skills Proficiency of 6- to 12-Year-Old Children - de Niet, M.; Platvoet, S. W. J.; Hoeboer, J. J. A. A. M.; de Witte, A. M. H.; de Vries, S. I.; Pion, J. (Frontiers in Education, 2021)
The main aim of this study was to determine the agreement in classification between the modified KörperKoordinations Test für Kinder (KTK3+) and the Athletic Skills Track (AST) for measuring fundamental movement skill levels (FMS) in 6- to 12-year old children. 3,107 Dutch children (of which 1,625 are girls) between 6 and 12 years of age were tested with the KTK3+ and the AST. The KTK3+ consists of three items from the KTK and the Faber hand-eye coordination test. Raw scores from each subtest were transformed into percentile scores based on all the data of each grade. The AST is an obstacle course consisting of 5-7 concatenated FMS that should be performed as quickly as possible. The outcome measure is the time needed to complete the track. A significant bivariate Pearson correlation coefficient of 0.51 was found between the percentile sum score of the KTK3+ and the time to complete the AST, indicating that both tests measure a similar construct to some extent. Based on their scores, children were classified into one of five categories: <5%, 5–15%, 16–85%, 86–95% or >95%. Cross tabs revealed an agreement of 58.8% with a Kappa value of 0.15 between both tests. Less than 1% of the children were classified more than two categories higher or lower. The moderate correlation between the KTK3+ and the AST and the low agreement in classifying children into five categories of FMS stress the importance of the test choice. When choosing a test, one needs to be aware of the context in which the test will be conducted, know which construct of motor competence you want to measure and know from the start what the purpose of testing is (e.g., screening or monitoring). Based on these considerations, the most appropriate assessment tool can be chosen.